KEY PROSPECTS FOR THE DEVELOPMENT OF THE DIGITAL ECONOMY IN UZBEKISTAN (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The article analyzes the development of the digital economy in Uzbekistan and its prospects in the context of the transformation of modern information. The goals and objectives of the digital economy in the country were also discussed in detail, as well as the importance of production processes were illustrated.